Solvent-controlled assembly of aromatic glutamic dendrimers for efficient luminescent color conversion - Xing, Pengyao (2020)
A binary supramolecular system where self-sorting and coassembly behavior can be switched by changing the solvent polarity is hereby reported. Glutamic dendron is separately conjugated with pyrene and naphthalimide luminophores through an alkyl spacer. The resulting structurally similar building units can self-assemble into one-dimensional micro/nanostructures with hexagonal and lamellar packing, respectively. Varying solvents from polar aqueous solution to nonpolar decane is evidenced to profoundly inverse the superchirality and switch self-sorted assembly to coassembly of the two building blocks. The moisture sensitivity of the naphthalimide moiety is considered the primary driving force for the self-sorting phenomenon in aqueous solution, resulting in inevitable hydration to repel its stacking with hydrophobic pyrene moiety. On the other hand, the naphthalimide unit can integrate segmentally with the pyrene unit in decane, greatly facilitating the nanofiber growth and supramolecular gel formation along with improved energy transfer efficiency between luminophores. As a result, the coassembly-based thin films show efficient luminescent color conversion upon the UV light irradiation. This research presents a useful route for the fabrication of controllable solution-processed light emitting devices from self-assembled multicomponent systems.